Comparative metabolomics analysis in the clean label ingredient of NFC spine grape juice processed by mild heating vs high pressure processing - Shini Yang; Lu Mi; Kewen Wang; Xue Wang; Jihong Wu; Meijun Wang; Zhenzhen Xu (Food Innovation and Advances, 2023)
Not from concentrate (NFC) fruit juice is the crucial clean label ingredient for new-style tea-making due to its pleasant color and fresh aroma. Here, we compared the effects of mild heating (MH) and high pressure processing (HPP) on physicochemical characters and phytochemicals in NFC spine grape juice based on metabolomics analysis. Similar compound profiles were observed between HPP-treated and fresh juices. The richer phytochemical compounds comprised malvidin-3-O-glucoside, malvidin-3,5-di-O-glucoside, quercetin-3-O-rhamnoside, quercetin-3-O-glucuronide, catechin, caffeic acid, ferulic acid, procyanidin B1, procyanidin B2 were obtained after MH treatment. Nine marker phenolics and two marker tripeptides (i.e., Glu-Val-Phe and Leu-Leu-Tyr) were identified to differentiate MH from HPP treatment, of which higher contents occurred in the MH group. Storage time experiments showed that the Glu-Val-Phe could serve as potential markers for monitoring storage of spine grape juice. These results provide new insights into the effects of processing on individual phytochemical changes and the guide for commercial application of production of spine grape NFC juice.